THE ROLE OF SPIROMETRY AND ITS BENEFIT TO ASSESS RESPIRATORY SYMPTOMS IN THE SEMERU VOLCANIC ERUPTION COMMUNITY SERVICES - Aditya Sri Listyoko; Susanthy Djajalaksana; Ngakan Putu Parsama Putra; Triwahju Astuti; Fitri Indah Sari; Nizzar Firdaus Trisnian; Silvy Amalia Falyani; Juwita Febriawati; Adinda Pramitra Permatasari; Claudia Herda Asyari (Journal of Community Health and Preventive Medicine, 2022)
Spirometry is a standard diagnostic tool for respiratory diseases. The people who live around the volcanic eruption may have a respiratory problems, both acute and chronic conditions. The aim of this study is to evaluate whether spirometry can be used as a diagnostic tool in the context of disaster in particular volcanic eruption. Data was obtained from medical examination in community services of Semeru volcanic eruption affected community in Pronojiwo, Oro Oro Ombo, Lumajang in last January 2022. Spirometry was performed for the patient who had a respiratory problems. Data was analyzed descriptively to assess lung function test using spirometry and its benefit in the people affected by volcanic eruption.  Among the subjects, 77.27% had abnormal findings from the spirometry result. The mean of %VC, % FVC and % FEV1/FVC were 71.49%; 74.58%; 74.39% respectively. The result of spirometry revealed normal, restriction, and obstruction with suggestive restriction 18.18%; 22.73%; 31.82%; 22.73% respectively. The evaluation of spirometry parameters showed that 54.55% was appropriate for clinical diagnosis made by a physician.  Our data show that most subjects had an abnormal results from spirometry. Spirometry may be a diagnostic tool can be used in natural disasters, particularly volcanic eruption for assessing respiratory symptoms.